Students Perceptions Regarding Culturally Sensitive Classrooms: A Case Study of Delhi Schools - Geeta Pathak; Febria Sri Artika (Jurnal Educative: Journal of Educational Studies, 2022)
India is known for its motto of unity in diversity. Delhi classrooms are mirrors of this diversity. The researchers, being in the capacity of teachers and educators, received regular feedback from trainee teachers regarding the classroom environment of secondary schools in Delhi. During those feedback sessions and in submitted reports on reflections, there were frequent entries on cultural alienation and cultural clashes. These entries forced the researchers to study the status of cultural sensitivity in secondary classrooms in Delhi. The study discusses the perceptions of students regarding their own cultural identity, their peers’ cultural identity, and shared experiences of cultural alienation, bullying, or conflicts in their classrooms. The study also discusses students’ expectations of their teachers in creating culturally sensitive classrooms. This is a descriptive study. Ex post-facto survey design was chosen for the study of culturally sensitive classrooms. The sample consists of 445 students in 12 schools in Delhi (five public and seven private). The self-prepared questionnaire for students called the Cultural Sensitivity Questionnaire for Students (CSQS) with CVR 0.68 was used as the tool. The study concluded that cultural alienation, bullying, and conflicts occur because of mutual ignorance of each other’s culture.